Rare e14a3 (b3a3) BCR-ABL Fusion in Chronic Myeloid Leukemia in India: The Threats and Challenges in Monitoring Minimal Residual Disease (MRD) - Salil Vaniawala; Arpan Acharya; Harsh Parekh; Pratap N. Mukhopadhyaya (Analytical Cellular Pathology)
Objective: The primary objective of this work was to confirm the occurrence of rare BCR ABL fusion variant involving the a3 region of the ABL gene in a patient positive for t(9;22) translocation but negative for common major and minor breakpoint cluster regions and the challenges and threats that it poses in a routine laboratory setting which use commercial kits for monitoring the minimal residual disease.